2007
DOI: 10.1007/s00109-007-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Properties of scyllo–inositol as a therapeutic treatment of AD-like pathology

Abstract: Inositol is a simple polyol with eight naturally occurring stereoisomers. myo-Inositol, D-chiro- and epi-inositol have been examined as potential therapeutic agents for various diseases, with favorable results, but treatment with scyllo-inositol has not been previously investigated. Our laboratory has shown that scyllo-inositol inhibits cognitive deficits in TgCRND8 mice and significantly ameliorates disease pathology, suggesting it might be effective in treating Alzheimer's disease (AD). In this paper, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 48 publications
7
101
0
2
Order By: Relevance
“…The mechanism of polyQ-Htt modulation may vary between compounds and be independent of direct interaction of the compound with mutant Htt. The decrease in polyQ-Htt aggregation after SI treatment is consistent with previous studies on A␤ peptide aggregation that demonstrated a decrease in A␤ oligomer and fibril formation in vitro (19,54), stabilization of preformed oligomers in vitro (54), and decreased oligomers and prevention of amyloid plaques in vivo (55)(56)(57). The lack of toxicity detected in this study is also in agreement with the SI-induced decrease in ␣-synuclein toxicity in an inducible neuronal cell model (21) and in amyloid-␤ peptide toxicity in the 7PA2 cell line (54).…”
Section: Discussionsupporting
confidence: 91%
“…The mechanism of polyQ-Htt modulation may vary between compounds and be independent of direct interaction of the compound with mutant Htt. The decrease in polyQ-Htt aggregation after SI treatment is consistent with previous studies on A␤ peptide aggregation that demonstrated a decrease in A␤ oligomer and fibril formation in vitro (19,54), stabilization of preformed oligomers in vitro (54), and decreased oligomers and prevention of amyloid plaques in vivo (55)(56)(57). The lack of toxicity detected in this study is also in agreement with the SI-induced decrease in ␣-synuclein toxicity in an inducible neuronal cell model (21) and in amyloid-␤ peptide toxicity in the 7PA2 cell line (54).…”
Section: Discussionsupporting
confidence: 91%
“…5,7 Scyllo-inositol also appears to neutralize toxic effects of A␤ oligomers, 6 including amelioration of oligomerinduced synaptic loss, LTP inhibition, and memory deficits. 8,9 A prior amyloid antiaggregation agent failed to demonstrate efficacy in phase 3 trials, 10 but several other amyloid-targeted therapies are currently being studied.…”
mentioning
confidence: 99%
“…[36] scyllo-Inositol is not incorporated into phospholipids in mammals. [37] The analogue 1-deoxy-1-fluoro-scyllo-inositol (96 Figure 3) inhibits the incorporation of myo-inositol into phosphatidylinositols. [38] scyllo-Inositol inhibits the incorporation of myo-inositol into lipid-soluble phosphoinositides and water-soluble inositol phosphates in the developing rat conceptus (causing dysmorphogenesis) and also impairs phosphoinositide hydrolysis.…”
Section: Biology and Medicinementioning
confidence: 99%
“…[78] Intracellular scyllo-inositol levels in rat brain extracts have been analysed by micellar electrokinetic chromatography. [79] 4.6 scyllo-Inositol Phosphates scyllo-Inositol is not incorporated into phospholipids in mammals [37] but scyllo-inositolcontaining phosphatidylinositol has been detected in non-mammalian species -see the Supporting Information (SI_2) for details.…”
Section: Scyllo-inositol and Diagnosticsmentioning
confidence: 99%